Both Prelimbic and Infralimbic Noradrenergic Neurotransmissions Modulate Cardiovascular Responses to Restraint Stress in Rats - Oliveira, Leandro A.; Pollo, Taciana R. S.; Rosa, Elinéia A.; Duarte, Josiane O.; Xavier, Carlos H.; Crestani, Carlos C. (Frontiers in Physiology, 2021)
The prelimbic (PL) and infralimbic (IL) subareas of the medial prefrontal cortex (mPFC) have been implicated in physiological and behavioral responses during aversive threats. The previous studies reported the noradrenaline release within the mPFC during stressful events, and the lesions of catecholaminergic terminals in this cortical structure affected stress-evoked local neuronal activation. Nevertheless, the role of mPFC adrenoceptors on cardiovascular responses during emotional stress is unknown. Thus, we investigated the role of adrenoceptors present within the PL and IL on the increase in both arterial pressure and heart rate (HR) and on the sympathetically mediated cutaneous vasoconstriction evoked by acute restraint stress. For this, bilateral guide cannulas were implanted into either the PL or IL of male rats. All animals were also subjected to catheter implantation into the femoral artery for cardiovascular recording. The increase in both arterial pressure and HR and the decrease in the tail skin temperature as an indirect measurement of sympathetically mediated cutaneous vasoconstriction were recorded during the restraint session. We observed that the microinjection of the selective α2-adrenoceptor antagonist RX821002 into either the PL or IL decreased the pressor response during restraint stress. Treatment of the PL or IL with either the α1-adrenoceptor antagonist WB4101 or the α2-adrenoceptor antagonist reduced the restraint-evoked tachycardia. The drop in the tail skin temperature was decreased by PL treatment with the β-adrenoceptor antagonist propranolol and with the α1- or α2-adrenoceptor antagonists. The α2-adrenoceptor antagonist into the IL also decreased the skin temperature response. Our results suggest that the noradrenergic neurotransmission in both PL and IL mediates the cardiovascular responses to aversive threats.